(untitled) (American Journal of Applied Statistics and Economics, 2023)
One of the main objectives of macroeconomic policy of most developing countries like Ethiopia is to attain sustainable economic growth together with stable price level. Price stability is considered as a proxy for macroeconomic stability, the ongoing high level of inflation is not a good sign. Large fluctuations in inflation for firms, consumers and the public sector reduce the economy in the long run growth potential. The nations of the countries who are highly affected by the problem of inflation are those who have low level of income or fixed income and unemployed portion of the population. Higher average inflation has a negative impact on the steady state growth. This is because of the higher cost of transaction that inflation causes to the money market. It is generally accepted that instability in the general level of prices causes substantial economic distortions, leading to inefficiencies, both in aggregate employment and output. Due to different factors, the effects of inflation have significant effect on economic growth in Ethiopia.